Brittle stars: a story of success in biodiversity - Beatty, Alex (My University, 2015)
The brittle star is found in a wide range of habitats all over the world. The regenerative and adaptive capabilities have allowed them to diversify. Huge photo evidence has determined several species to be invasive as they disperse into new habitats.
Keywords: brittle stars; marine animals